A governance framework for blockchain technology in the South African insurance industry - Damon, Aldo (Department of Information Systems, 2025)
Purpose: The governance of blockchain technology is a topic of continuing study, and a multidisciplinary perspective on blockchain governance is essential for building a formal governance framework for this emerging technology. While the subject of blockchain governance is sometimes misunderstood, blockchain technology has gained growing interest from businesses and academics. Blockchain stakeholders cannot work or make rational decisions optimally without enough insight into the governance of blockchains. Its advancement and stabilization are of utmost importance for stakeholders that depend on blockchain. Where organizations and individual end-users must consider in their decision the element of regulation for the blockchain technology or network, regulators and developers still need to grasp it. The purpose of this study is to explore the understanding of blockchain governance by reporting on frameworks and themes that capture the main dimensions and layers of blockchain governance. The study proposes a governance framework that can assist strategic management within businesses to analyse the governance of the blockchain in a comprehensible manner in order to facilitate strategic decision-making in the insurance industries within South African organisations. Design/methodology/approach: This deductive qualitative research that is shaped by subjectivism ontology, interpretive epistemology, uses comprehensive literature review and deductive thematic analysis of eight semi-structured and focus group interviews for data collection, which then identifies the key dimensions and layers of blockchain governance, including technical, economic, social, and legal aspects of consideration. The deductive thematic analysis selected follows the seven steps of deductive qualitative research. Findings: The innovative blockchain governance framework consists of four perspectives, each tied to key themes from the collected data. The OSS Governance Phases focus on decision-making, community engagement, and conflict resolution. The OSS Life Cycle Stages emphasize onboarding, code contribution, and version control. The Blockchain Governance Framework Dimensions & Layers highlight on chain voting, off-chain communication, and incentive structures. Lastly, the TOE Framework Model addresses technological readiness, organizational roles, and regulatory compliance. These perspectives align with the study's findings, ensuring clarity and alignment with research objectives. xi P a g e Research limitations/implications: The paper contributes to blockchain governance theory. The innovative perspectives provide a synthesized conceptual framework for researchers to evaluate and understand blockchain governance development from multiple perspectives. Practical implications: The synthesized blockchain governance framework presents a road map for practitioners and business managers to follow in their blockchain projects. Originality/value: The research uses an innovative perspectives and other individual research methodologies to synthesize the existing research framework proposed. It is one of the first research papers in the information systems field to make use of deductive thematic analysis approach to consolidate the existing qualitative research and interviews to systematically propose a blockchain governance framework.